SPARCL1-containing neurons in the human brainstem and sensory ganglion. (2nd April 2016) - Hashimoto, Naoya; Sato, Tadasu; Yajima, Takehiro; Fujita, Masatoshi; Sato, Ayumi; Shimizu, Yoshinaka; Shimada, Yusuke; Shoji, Noriaki; Sasano, Takashi; Ichikawa, Hiroyuki
Abstract: Secreted protein, acidic and rich in cysteine-like 1 (SPARCL1) is a member of the osteonectin family of proteins. In this study, immunohistochemistry for SPARCL1 was performed to obtain its distribution in the human brainstem, cervical spinal cord, and sensory ganglion. SPARCL1-immunoreactivity was detected in neuronal cell bodies including perikarya and proximal dendrites, and the neuropil. The motor nuclei of the IIIrd, Vth, VIth, VIIth, IXth, Xth, XIth, and XIIth cranial nerves and spinal nerves contained many SPARCL1-immunoreactive (-IR) neurons with medium-sized to large cell bodies. Small and medium-sized SPARCL1-IR neurons were distributed in sensory nuclei of the Vth, VIIth, VIIIth, IXth, and Xth cranial nerves. In the medulla oblongata, the dorsal column nuclei also had small to medium-sized SPARCL1-IR neurons. In addition, SPARCL1-IR neurons were detected in the nucleus of the trapezoid body and pontine nucleus within the pons and the arcuate nucleus in the medulla oblongata. In the cervical spinal cord, the ventral horn contained some SPARCL1-IR neurons with large cell bodies. These findings suggest that SPARCL1-containing neurons function to relay and regulate motor and sensory signals in the human brainstem. In the dorsal root (DRG) and trigeminal ganglia (TG), primary sensory neurons contained SPARCL1-immunoreactivity. The proportion of SPARCL1-IR neurons in the TG (mean ± SD, 39.9 ± 2.4%) was higher than in the DRG (30.6 ± 2.1%). SPARCL1-IR neurons were mostly medium-sized to large (mean ± SD, 1494.5 ± 708.3 μm 2 ; range, 320.4–4353.4 μm 2 ) in the DRG, whereas such neurons were of various cell body sizes in the TG (mean ± SD, 1291.2 ± 532.8 μm 2 ; range, 209.3–4326.4 μm 2 ). There appears to be a SPARCL1-containing sensory pathway in the ganglion and brainstem of the spinal and trigeminal nervous systems.